PENGARUH LATIHAN BOX JUMP DAN DEPTH JUMP TERHADAP KEMAMPUAN JUMP SHOOT PADA TIM BOLA BASKET PUTRI SMA NEGERI 1 DEMAK TAHUN 2022 - Lisa Andani Putri; Anggit Wicaksono (Unnes Journal of Sport Sciences, 2023)
This research is about the effect of box jump and depth jump training on jump shoot ability in the women's basketball team at SMA Negeri 1 Demak. The purpose of this study was to determine the effect of box jump and depth jump training on the ability to jump shoot on the women's basketball team at SMA Negeri 1 Demak. The research method uses a quantitative type with experimental methods and matched subject design with ordinal pairing techniques. The instrument used is the speed spot shooting test. The research sample was 10 participants of the women's basketball team at SMA Negeri 1 Demak. The data analysis technique used the T test. T test results: sig. (2-tailed) pre-test and post-test box jump 0.001<0.05 with a t-count value of 9.021>t table 2.306. sig value. (2-tailed) pre-test and post-test depth jump 0.002 <0.05 with a t value of 7.483> t table 2.306 then Ho is rejected and Ha is accepted so that it means that there is an influence between box jump and depth jump training on increasing jump shoot ability SMA Negeri 1 Demak women's basketball team. Value of Sig. (2-tailed) post-test box jump and post-test depth jump 0.727> 0.05 with a t-count value of 0.362 <t table 2.306 then Ho is accepted and Ha is rejected so that it means that there is no difference in average between the results of the post-test box jump and post-test depth jump. Plyometric box jump and depth jump exercises can improve the jump shoot ability by increasing the components of the physical condition needed in the jump shoot technique.